Examining the route from perceived organizational support to psychological symptoms of white-collar workers: a serial mediation path model - Taskale, Nermin; Ozveren, Cem Guney; Halacoglu, Asli; Yalcin, Rumeysa Cemre (TAYLOR & FRANCIS LTD, 2026)
It is considered important for employees to be able to establish a work-life balance during the adaptation process for changes and managing circumstances that negatively affect their psychological well-being and may cause depression and anxiety as the result of stress factors. The current study aimed to analyze the relationships among perceived organizational support, work-family conflict, cynicism about organizational change, job-related affective well-being and psychological symptoms of white-collar workers. The sample consisted of 202 white-collar workers from urban cities in Turkey. The results from structural equation modeling revealed a good fit for the data. Work-family conflict, organizational change cynicism and job-related affective well-being were found to serially mediate the path from perceived organizational support to psychological symptoms such as depression, anxiety and stress. These findings provided an important contribution to the literature by presenting a new and original research model.
Keywords: white-collar workers; perceived organizational support; work-family conflict; cynicism about organizational change; job-related affective well-being; psychological symptoms; SOCIAL-EXCHANGE THEORY; FAMILY CONFLICT; DEPRESSION ANXIETY; IMPACT; COMMITMENT; PERSONALITY; CYNICISM; VALIDITY; HEALTH; DASS; Engineering; Public, Environmental & Occupational Health